Is Low Level of Serum Ionized Magnesium Responsible for Eclampsia? (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Objective: To determine the level of serum ionized magnesium in eclampsia patient before and 24 hours after giving the loading dose of magnesium sulfate and if low, to determine the relationship between levels of ionized magnesium in serum and occurrence of eclamptic convulsions. Methods: Fifty eclampsia patients received a loading dose of 4 gm of magnesium sulfate, which was diluted with 12 ml of distilled water and then was given intravenously over a period of 10-15 minutes and it was followed by 3 gm of magnesium sulfate deep intramuscular injection in each buttock. Patient's venous blood samples were obtained before and 24hours after loading dose of magnesium sulfate and analyzed for ionized magnesium, sodium, potassium, and calcium level. Results: Level in eclampsia women is 0.47 (0.15-1.04) m mol/L and 0.74 (0.20-2.00) m mol/L before and 24 hours after treatment with loading dose of magnesium sulfate, respectively .This change is significant.( P value is < 0.001) . Change in ionized magnesium level associated with change in diastolic and systolic blood pressure, mean arterial pressure and albuminuria .This changes are also significant (p